Innovation and Competitive Intelligence in Business. A Bibliometric Analysis. - De-las-Heras-Rosas, Carlos Javier; Herrera-Ballesteros, Juan (MDPI, 2021)
The business environment of today is complex and dynamic due to increasing global competition. The businessman needs to master and know all the information that has strategic value, and Competitive Intelligence is positioned as the most appropriate tool to achieve this goal. In recent decades, research and publications related to Competitive Intelligence have been increasing, although the military heritage of this field of research and the association with large corporations has meant that the literature is still at an early phase of development and specialisation. This paper analyses scientific articles on Competitive Intelligence from journals in the Web of Science database between 1985 and 2021. The main objective of this research has been to detect the topics that have been most related to Competitive Intelligence. The 589 papers analysed indicate that interest in this topic is relatively recent and that the most central topic in the sample is Innovation. The bibliometric analysis carried out indicates that Competitive Intelligence is closely linked to innovation processes in companies, facilitating its development. Furthermore, it highlights the importance that business management, together with the promotion of absorptive capacity and alignment around Competitive Intelligence will allow companies to improve their competitive advantages, as well as greater success with new products. Little research was found on aspects related to small and medium-sized enterprises and patents in relation to Competitive Intelligence. This research aims to show which are the most researched topics in relation to Competitive Intelligence, so that it can serve as support for future research, as well as for company managers in making decisions in relation to this topic.
Keywords: Inteligencia económica; Negocios; Planificación estratégica; SciMAT; Competitive intelligence; Innovation; Business intelligence